Stereotaxic Exposure of the Central Nucleus of the Amygdala to Corticosterone Increases Colonic Permeability and Reduces Nerve-Mediated Active Ion Transport in Rats - Hattay, Priya; Prusator, Dawn K.; Johnson, Anthony C.; Greenwood-Van Meerveld, Beverley (Frontiers in Neuroscience, 2018)
Background: Irritable bowel syndrome (IBS) is characterized by visceral pain and abnormal bowel habits that are worsened during stress. Evidence also suggests altered intestinal barrier function in IBS. Previously, we demonstrated that stereotaxic application of the stress hormone corticosterone (CORT) onto the central nucleus of the amygdala (CeA) induces colonic hyperalgesia and anxiety-like behavior in a rat model, however the effect on intestinal permeability and mucosal function remain to be evaluated. Methods: Male Fischer 344 rats underwent bilateral stereotaxic implantation of CORT or inert cholesterol (CHOL)-containing micropellets (30μg) onto the dorsal margin of the CeA. Seven days later, colonic tissue was isolated to assess tissue permeability in modified Ussing chambers via transepithelial electrical resistance (TEER) and macromolecular flux of horseradish peroxidase (HRP). Secretory responses to electrical field stimulation (EFS) of submucosal enteric nerves as well as activation with forskolin were used to assess movements of ions across the isolated colonic tissues. In a separate cohort, colonic histology and mast cell infiltration was assessed. Key Results: Compared to CHOL-implanted controls, we determined that exposing the CeA to elevated levels of CORT significantly increased macromolecular flux across the colonic epithelial layer without changing TEER. Nerve-mediated but not cAMP-mediated active transport was inhibited in response to elevated amygdala CORT. There were no histological changes or increases in mast cell infiltration within colonic tissue from CORT treated animals. Conclusion and Inferences: These observations support a novel role for the CeA as a modulator of nerve-mediated colonic epithelial function.